A Study on the Linguistic Means Used In Advertisement: - (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Advertising traces its history back to ancient times.First forms of advertising messages were transferred by word of mouth, however,in the ruins of Pompeii commercial messages and election campaign displays havebeen found. Egyptians used Papyrus to create sales messages and wall posters,while in Greece and Rome lost-and-found advertising on papyrus was common. Wallor rock painting for commercial advertising is another manifestation of anancient media advertising form, which is present to this day in many parts ofAsia, Africa and South America. With the form of advertising, we could meet in themarketplaces, where the sellers used to shout and extol their products. In thecourse of time, people more and more tried to differentiate their products andbegan to find out new ways of presenting. They started to accentuate the visualaspect of the advertisement. With the expansion of colour printing and colorfulposters the streets began to revel in colors. These posters were ancestors toour modern billboards.